2013
DOI: 10.1117/1.oe.52.10.104107
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the cementitious materials subjected to sulfate attack with optical fiber excitation Raman spectroscopy

Abstract: Abstract. Formation of ettringite and gypsum from sulfate attack together with carbonation and chloride ingress have been considered as the most serious deterioration mechanisms of concrete structures. Although electrical resistance sensors and fiber optic chemical sensors could be used to monitor the latter two mechanisms on site, currently there is no system for monitoring the deterioration mechanisms of sulfate attack. In this paper, a preliminary study was carried out to investigate the feasibility of moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Surprisingly, up to date, the application of optical fibre Raman system in monitoring the durability of concrete structure has not been attempted in the literature. Previous study carried out by the authors showed that there is a good potential to monitor sulphate attack with optical fibre Raman spectroscopy [7]. This paper, therefore, extends the previous work to explore the potential of using optical fibre Raman system to monitor the carbonation mechanism of concrete.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…Surprisingly, up to date, the application of optical fibre Raman system in monitoring the durability of concrete structure has not been attempted in the literature. Previous study carried out by the authors showed that there is a good potential to monitor sulphate attack with optical fibre Raman spectroscopy [7]. This paper, therefore, extends the previous work to explore the potential of using optical fibre Raman system to monitor the carbonation mechanism of concrete.…”
Section: Introductionsupporting
confidence: 63%
“…In the case of optical fibre Raman system, this could also include optics alignment and initial optimisation. In the current study, the bench-mounted Raman and optical fibre Raman systems were calibrated through the same methodology as the previous work [7] by using the well-defined Raman peak of silicon wafer at 520.2 ± 0.5 cm -1 [36]. Figs.…”
Section: Calibration Of Raman Spectroscopy (With/without Optical Fibre)mentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of portable instrumental configurations of Raman spectrometers opens doors to the possibility of developing a diagnostic tool for ASR gels that can be deployed in the field. A similar approach to investigate the feasibility of applying a portable configuration of Raman spectroscopy to monitor sulfate attack has been recently published [14]. The fiber optic probe of a portable Raman spectrometer can focus the laser beam into cracks of ASR-damaged concrete and potentially collect the Raman signal of gel deposits.…”
Section: Introductionmentioning
confidence: 98%
“…An important point to be noted is that most of the research efforts focus on characterization of white cement, synthetic calcium silicate hydrate (C-S-H), and hydration of pure cement phases due to the fluorescence associated with the analysis of grey cements [5,8,11]. Raman spectroscopy has also been used successfully to investigate other hydration products such as sulfate phases and hydroxides [5,[12][13][14][15] and to study carbonation [8,16] and secondary deposits of sulfate attacked concrete [12,14].…”
Section: Introductionmentioning
confidence: 98%